And, I mean every word of it: Comments on Francis Dupuis-Déri’s “Global Protesters Versus Global Elite: Are Direct Action and Deliberative Politics Compatible ?” - Johnson, Genevieve (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
Focusing on how recent protests centered on global economic and environmental injustices can contribute to furthering deliberative politics and realizing deliberative democracy, Francis Dupuis-Déri examines the important and historical tension between force and persuasion. However, casting protest as legitimate in the framework of deliberative politics and as serving deliberative democracy obscures its own value in endeavors to achieve social, economic, and environmental justice. Being sympathetic to Dupuis-Déri’s work, I wish to make several, interrelated conceptual and practical clarifications in order to bring back to the fore the fundamental importance of protest, in terms of contributions not to deliberative politics and deliberative democracy but to public discourse.